Evaluation of surface treatment and gamma irradiation on the performance of palm fiber/natural rubber biocomposites. Issue 5 (3rd May 2020) - EL-Zayat, Mai M.; M. Mohamed, Rania; Raslan, Heba A.
Abstract: The paper investigates the impact of applying different methods of matrix/fiber surface modification of natural rubber/palm fiber blend aiming at developing advanced bio-composites eligible for vast implementation areas. The synergistic effect of gamma irradiation associated with the matrix interfacial chemical modification using maleic anhydride was evaluated. The chemical modification efficiency was verified by FTIR analysis and morphologically by SEM techniques. Likewise, the fabricated bio-composites were mechanically examined through tensile strength and elongation at break percentage measurement and thermally analyzed by TGA. The FTIR spectra demonstrated the characteristic functional groups of maleic anhydride and the reduction of fiber OH bonds. SEM characterization ensured alteration in fiber morphology, suggesting the positive mutual influence of irradiation and chemical modification on the dimensional stability and the enhancement in the mechanical properties of interest against the recorded features of the pristine samples.